EFFECT OF PHYSICAL EFFORT ON RATE OF CARDIAC CONTRACTION TIME, BLOOD FLOW IN CORONARY ARTERY, AND MYOCARDIAL OXYGEN CONSUMPTION AMONG YOUTH SOCCER PLAYERS - Prof. Dr. Ammar Jasim Muslim; Prof. Dr. Falah Mahdi Abood; Prof. Dr. Sadeq Abbas Ali (Proximus Journal Publishing, 2024)
Physical effort that takes place in football matches or what coaches in the training units is formulated in a way that affects the most important muscle in the body, which is the heart muscle, which has a very important role in affecting the rest of the body. Therefore, exercises must be monitored and what happens to heart muscle during the implementation of physical efforts with different stress, and from here the importance of research in the extent of the effect of physical effort on heart muscle responses to explain the percentage of cardiac contraction and what affects the venous return to the heart and the level of oxygen carried by the blood. Hence the problem can be formulated with the following question: What is effect that heart rate is high on the time of cardiac contraction, the nourishment of heart in blood and the amount of oxygen that is connected to it? The research also aims to identify the differences in the heart rate, the percentage of cardiac contraction, the amount of blood flow in the coronary artery and amount of oxygen consumed between the two physical voltages. The researchers also touched on the descriptive approach to a sample of the youth football category, which numbered (6 players) for the season (2023-2024) in Basrah Governorate. researchers also measured the variables, the amendment of the heartbeat, the percentage of cardiac contraction, amount of blood flow in the coronary artery, amount of consumer oxygen during rest, and after physical effort at a speed (8 km) and (12 km) and at an angle of deviation (zero). Thus, the researchers concluded. 1- There is a variation in the level of heart rate, percentage of cardiac contraction, amount of blood flow in coronary artery and amount of consumer oxygen after performing two physical effort on members of research sample.
Keywords: physical effort; coronary artery; myocardial oxygen consumption